QT/QTc safety and efficacy evaluation of teneligliptin in Indian type 2 diabetes mellitus patients: the “thorough QT/QTc” study (Q-SET study) - Erande S (Dove Medical Press, 2019)
S Erande,1 S Sarwardekar,2 B Desai31Department of Medicine, Akshay Hospital, Pune 411004, India; 2Department of Medicine, Sawardekar Clinic, Mumbai 400055, India; 3Department of Cardiology, Desai Heart Care Clinic, Mumbai 400092, IndiaBackground: Newer therapies, such as dipeptidyl peptidase-IV inhibitors, are increasingly being used in the treatment of type 2 diabetes mellitus (T2DM). Teneligliptin, a DPP4 inhibitor, currently commonly used as monotherapy or as add-on therapy, was generally well tolerated in patients with T2DM during clinical trials. No AEs related to QT prolongation were detected with 40 mg/day of teneligliptin, but were seen at a supratherapeutic dose of 160 mg/day.Aims and objective: To evaluate the safety of teneligliptin in type 2 diabetes patients with respect to QTc prolongation.Methodology: This was an open-label, prospective, multi-centric trial conducted in patients with T2DM aged ≥18 to ≤65 years with a hemoglobin A1c (HbA1c) ≥7.0% and gliptin naïve. Teneligliptin 20 mg once a day was added to the standard treatment. The dose of teneligliptin was increased to 40 mg once a day if required, on the basis of glycemic parameters. Twelve-lead ECG was recorded at baseline and follow-up visits. The QTc was calculated by using the Bazett’s formula (QTc=QT/√RR).Results: The mean QT interval at screening (Visit 1, Day 0, baseline ECG) was 0.33±0.07 seconds, while at visit 2 (Day 1, post 2 hours of Teneligliptin dosing) it was 0.32±0.04 seconds, at visit 3 (Day 15) it was 0.32±0.04 seconds, and at visit 4 (Day 90) it was 0.32±0.03 seconds. The mean QTc interval at baseline was 0.37±0.04 seconds, while at visit 2 it was 0.37±0.04 seconds, at visit 3 it was 0.37±0.03 seconds, and at visit 4 it was 0.37±0.03 seconds. There was a significant reduction in fasting blood glucose (P=0.002), postprandial blood glucose (P<0.001), and HbA1c (P<0.001) at the end of the 3 months as compared to baseline.Conclusion: Teneligliptin at a therapeutic dose of 20 mg/day or 40 mg/day improved glycemic parameters significantly and did not cause QT/QTc interval prolongation.Keywords: diabetes, teneligliptin, QT prolongation